Photoinduced hole hopping through tryptophans in proteins - Záliš, Stanislav; Heyda, Jan; Šebesta, Filip; Winkler, Jay R; Gray, Harry B; Vlček, Antonín (Proceedings of the National Academy of Sciences - PNAS, 2021)
Hole hopping through tryptophan/tyrosine chains enables rapid unidirectional charge transport over long distances. We have elucidated structural and dynamical factors controlling hopping speed and efficiency in two modified azurin constructs that include a rhenium(I) sensitizer, Re(His)(CO) (dmp) , and one or two tryptophans (W , W ). Experimental kinetics investigations showed that the two closely spaced (3 to 4 Å) intervening tryptophans dramatically accelerated long-range electron transfer (ET) from Cu to the photoexcited sensitizer. In our theoretical work, we found that time-dependent density-functional theory (TDDFT) quantum mechanics/molecular mechanics/molecular dynamics (QM/MM/MD) trajectories of low-lying triplet excited states of Re (His)(CO) (dmp) -W (-W ) exhibited crossings between sensitizer-localized (*Re) and charge-separated [Re (His)(CO) (dmp )/(W or W )] (CS1 or CS2) states. Our analysis revealed that the distances, angles, and mutual orientations of ET-active cofactors fluctuate in a relatively narrow range in which the cofactors are strongly coupled, enabling adiabatic ET. Water-dominated electrostatic field fluctuations bring *Re and CS1 states to a crossing where *Re(CO) (dmp) ←W ET occurs, and CS1 becomes the lowest triplet state. ET is promoted by solvation dynamics around *Re(CO) (dmp) (W ); and CS1 is stabilized by Re(dmp )/W electron/hole interaction and enhanced W solvation. The second hop, W ←W , is facilitated by water fluctuations near the W /W unit, taking place when the electrostatic potential at W drops well below that at W Insufficient solvation and reorganization around W make W ←W ET endergonic, shifting the equilibrium toward W and decreasing the charge-separation yield. We suggest that multiscale TDDFT/MM/MD is a suitable technique to model the simultaneous evolution of photogenerated excited-state manifolds.